MENINGKATKAN KEMAMPUAN MENENTUKAN ISI DAN SAMPIRAN PANTUN DENGAN MENGGUNAKAN METODE INDEX CARD MATCH PADA SISWA KELAS VII MTsN BANJAR SELATAN 1 KOTA BANJARMASIN - Isabella, Anna (Vidya Karya Jurnal Kependidikan, 2015)
This research is a classroom action research (PTK) consisting of two cycles of the three meetings. Each cycle includes stages that are interconnected and continuous, namely planning, action, observation and reflection. The subjects were students of class VII MTs South Banjar 1 Banjarmasin in the school year 2013/2014 the number of students 24. These results demonstrate the applicability of the method Index card can match and improve the ability to determine the content of and rhymes of Sampiran class VII MTsN South Banjar 1 City Banjarmasin. It is declared a success. The first cycle of the average value of 76 increased by 88 and 71 and 87 with classical completeness and individually. The activity of teachers has risen in the first cycle reaches an average of 62%, increasing to 75% and reaches 100%. Activities of students has increased an average of 58%, 74% and 84%. The activity group work on learning the first category increased enough into either category. The response of students to the learning method index card match is that students feel happy, to have new experiences and very helpful in learning, have the courage to answer any questions or make an active and creative in order to understand the material by determining the content.